PERANAN E-PAYMENT SYSTEM ONLINE TERHADAP EFISIENSI PELAYANAN PUBLIK PADA PERUSAHAAN JAMSOSTEK CABANG 1 DI KOTA BATAM - Desi Sariani (Computer Based Information System Journal, 2015)
This study aimed to analyze the implementation of E-payment System Online on the efficiency of public services at PT. Jamsostek Cabang 1 - Batam using simple linear regression method. And data collected by a questionnaire survey to 120 respondents. This study provides input for PT. Jamsostek Cabang 1 Batam which help in process transactions effectively and efficiently so that the customer will be satisfied as consideration for the progress of the service provider. As for some of the conclusions of this study are as follows: The Role of E-Payment System Online on the efficiency of public services PT Jamsostek Branch 1 Batam. This means that the role well and giving the latest information and the ease of getting information to the E-Payment System Online, it will increase the efficiency of public services PT Jamsostek Branch 1 Batam.